The final curtain the art of dying on stage - Senelick, Laurence (Anthem studies in theatre and performance, 2022)
"It is a book about dying, or, more accurately, about the representation of dying in the theatre. Its chief concern is how actors undertook to translate words and concepts into forms legible and significant to an audience. It deals with the ways in which playwrights wrote about death and attitudes towards death in their cultures. Nevertheless, the emphasis is on the practice of acting"--